Recuperação de amidos remanescentes em resíduos de extração da fécula de mandioca - Battaglini, Neusa Maria Pavão [UNESP]; Cabello, Cládio [UNESP]; Coutinho, Ana Paula Cerino; Tokura, Ricardo Kazuyuki [UNESP] (My University, 2010)
This study had as objective analyzes the recovery of the residual starch due to the process of extraction of starch in cassava residues. The conventional enzymatic treatment for the recovery of the residual starch that one find encapsulated inside of the cells in the amyloplasts and also linked to the cellular wall it requests an agitation system and mixture, that it accomplishes the contact of the catalyst efficiently and simultaneously wall light an optimized energy the this operation. In this study, the sample lignocelulosic was agitated in a tank that worked as reactor, for certain time, in different concentrations of enzymes, rotations and to constant temperatures. In each rehearsal, they were certain the characteristics of the final product, as the density, viscosity and the concentrations of residual starch and sugars total reducers. The movement of the product inside the tank was verified adding a blue color. The best income of the process happened when they were used: time of process 80 minutes; concentration of enzymes 1,5 KNU / g of starch; agitation 15 rpm and temperature 80oC and the recovery of the starch was of 69,3%, with a consumption of energy of 34,7J.

Este estudo teve como objetivo analisar a recuperação do amido residual decorrente do processo de extração de amido em resíduos de mandioca. O tratamento enzimático convencional para a recuperação do amido residual que se encontra encapsulado dentro das células nos amiloplastos e também ligados à parede celular requer um sistema de agitação e mistura, que realize eficientemente o contato do catalisador e simultaneamente aplique uma otimizada energia a esta operação. Neste estudo, a amostra ligno-celulósica foi agitada em um tanque que funcionou como reator, por tempo determinado, em diferentes concentrações de enzimas, rotações e à temperaturas constantes. Em cada ensaio, foram determinadas as características do produto final, como a densidade, viscosidade e as concentrações de amido residual e açúcares redutores totais. O melhor rendimento do processo ocorreu quando foram utilizados: tempo de processo 80 minutos; concentração de enzimas 1,5 KNU/ g de amido; agitação 15 rpm e temperatura 80º C sendo que a recuperação do amido foi de 69,3% com um consumo de energia de 34,7J.
Extraction of starches in cassava residue
Keywords: Starch; Enzyme; Agitation; Amido; Enzima; Agitação